2019
DOI: 10.20944/preprints201911.0083.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From Allostatic Agents to Counterfactual Cognisers: Active Inference, Biological Regulation, and The Origins of Cognition

Abstract: What is the function of cognition? On one influential account, cognition evolved to co-ordinate behaviour with environmental change or complexity (Godfrey-Smith 1996). Liberal interpretations of this view ascribe cognition to an extraordinarily broad set of biological systems – even bacteria, which modulate their activity in response to salient external cues, would seem to qualify as cognitive agents. However, equating cognition with adaptive flexibility per se glosses over important distinctions in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 175 publications
(235 reference statements)
0
48
0
Order By: Relevance
“…Of course, autonomic regulation alone is not sufficient to ensure continued existence -to avoid hunger or thirst the animal must engage actions, such as seeking out food and water. Collectively, these actions are termed allostasis, the process via which the brain regulates the needs of the body (Corcoran & Hohwy, 2018;Corcoran, Pezzulo, & Hohwy, 2019;Schulkin & Sterling, 2019). Crucially, to stay viable on longer timescales, this action must be anticipatory -avoiding dyshomeostatic conditions before they arise Sterling, 2012).…”
Section: Homeostasismentioning
confidence: 99%
“…Of course, autonomic regulation alone is not sufficient to ensure continued existence -to avoid hunger or thirst the animal must engage actions, such as seeking out food and water. Collectively, these actions are termed allostasis, the process via which the brain regulates the needs of the body (Corcoran & Hohwy, 2018;Corcoran, Pezzulo, & Hohwy, 2019;Schulkin & Sterling, 2019). Crucially, to stay viable on longer timescales, this action must be anticipatory -avoiding dyshomeostatic conditions before they arise Sterling, 2012).…”
Section: Homeostasismentioning
confidence: 99%
“…It has recently been suggested that cognition requires a functional organization in which agents are able to detach from the present moment and engage in counterfactual active inference (Corcoran et al, 2019). IWMT does not have a clear position on whether or not the word "cognition" ought to be reserved for systems capable of generating counterfactual simulations.…”
Section: Against Strong Panpsychismmentioning
confidence: 99%
“…3. Conscious access-and possibly phenomenal consciousness-likely requires generative processes capable of counterfactual modeling (Friston, 2018;Pearl and Mackenzie, 2018;Corcoran et al, 2019;Kanai et al, 2019) with respect to selfhood and self-generated actions. In what follows I attempt to justify these claims by integrating across leading theories of emergent causation and consciousness.…”
Section: The Enduring Problems Of Consciousnessmentioning
confidence: 99%
“…The DMN and its imaginative capacities (Beaty et al, 2014(Beaty et al, , 2015Hassabis et al, 2014) may instantiate this kind of (informational) creative dynamo, constituting sources of strongly internally coherent predictions, so being capable of temporarily absorbing and then releasing free energy via the shaping of perception and driving of action. The network properties of the DMN are ideally suited to serve these functions, having both high centrality-and so high potential for integrating information and exerting control -while also being located distally from primary modalities, and so being capable of supporting dynamics that are more decoupled from immediate sensorimotor engagements (Sormaz et al, 2018;Corcoran et al, 2019). Further, the DMN is likely to support some of the most stable inferences available to embodied-embedded persons, with major nodes allowing for egocentric perspective-i.e., providing a subjective point of view in generating world models with spatial, temporal, and causal coherence-integrated memory, and even the foundations of selfhood (Hassabis and Maguire, 2009;Northoff, 2012;Brewer et al, 2013;Dennett, 2014;Davey and Harrison, 2018).…”
Section: Fep-ai + Iit + Gnwt = Iwmtmentioning
confidence: 99%
See 1 more Smart Citation